Fundamental Research in Oncology and Thrombosis 2 (FRONTLINE 2): A Follow‐Up Survey. (8th May 2020) - Kakkar, Ajay K.; Bauersachs, Rupert; Falanga, Anna; Wong, John; Kayani, Gloria; Kahney, Alex; Hughes, Rodney; Levine, Mark
Abstract: Background: Fundamental Research in Oncology and Thrombosis (FRONTLINE) is a global survey of physicians' perceptions and practice in the management of venous thromboembolism (VTE) in patients with cancer. Materials and Methods: The present survey, FRONTLINE 2, follows the original FRONTLINE survey (published in The Oncologist in 2003) and provides insights into how physicians perceive risk of VTE in cancer and approach its prophylaxis and treatment. Results: Between November 2015 and February 2016, 5, 233 respondents participated, representing cancer physicians and surgeons. Most believed that less than one in five patients with any cancer might be at risk of VTE, with a slightly higher risk in patients with brain, pancreatic, and lung tumors. The most frequently reported reasons for giving prophylaxis were prior history of VTE (74.6%), abnormal platelet count (62.0%), and obesity (59.5%). In surgical and medical cancer patients, low‐molecular‐weight heparin (LMWH) was the most popular prophylactic measure, used by 74.2% and 80.6%, respectively. Oral anticoagulants (OACs) were given in less than one fifth of cases. In surgical patients, prophylaxis was usually provided for 1 month postoperatively. Following a diagnosis of VTE, patients initially received treatment with LMWH and were maintained long term on OACs, primarily warfarin, dabigatran, and rivaroxaban. Most surgical and medical cancer patients underwent treatment of VTE for 3–6 months. Conclusion: Compared with the original FRONTLINE survey, FRONTLINE 2 reveals some differences in the management of VTE in patients with cancer. Newer anticoagulants such as fondaparinux, dabigatran, and rivaroxaban are being incorporated into the contemporary management of VTE in patients with cancer. Implications for Practice: This globally conducted survey of more than 5, 000 cancer clinicians revealed a number of insights into the perceived risk for venous thromboembolism as well as contemporary approaches to its prevention and treatment. Although guidelines have consistently recommended anticoagulant medications for prevention and treatment of cancer‐associated thrombosis, clinicians report substantial variation in their practice. Abstract : Improvements in molecular analysis hold promise for improved identification and treatment of cancers of unknown primary. This article presents the case of a patient with a cancer of unknown primary and metastases in the brain and lung, detailing the genomic profiling performed to establish targeted therapy options.